PENGARUH IKLIM DAN BUDAYA SEKOLAH TERHADAP TINDAKAN KEKERASAN VERBAL YANG DI LAKUKAN SISWA DI SEKOLAH - Fiki Setiyawan; Didik Tri Setiyoko; Farhan Saefudin Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of school climate and school culture on verbal violence committed by students at school. This study uses a quantitative approach with a survey method, and data collection techniques in the form of a Likert scale questionnaire, with a saturated sample technique. The results of this study indicate that school culture has a significant influence on verbal violence committed by students, while school climate does not provide a significant influence partially. This is evidenced by the t test which shows a significance value of the school culture variable of 0.002 with a calculated t value of 3.337, greater than the t table of 2.045. On the other hand, the school climate variable has a significance value of 0.125 with a calculated t value of 1.580, which means it is smaller than the t table and is not significant. However, based on the F test, the results show that simultaneously school climate and school culture have a significant influence on verbal violence committed by students. The results of the F test show a calculated F value of 13.034 and a significance of 0.000, less than 0.05. Based on the research findings, only school culture has been proven to directly influence verbal violence committed by students at school. However, when examined simultaneously, both school climate and culture have made significant contributions to this behavior.